Can green financial policies promote green urbanization? Evidence from China - Ma, Rong; Xi, Cunhu (Frontiers in Sustainable Cities, 2025)
This study investigates the impact of China’s green financial reform pilot zones on urban green development, with the aim of identifying whether financial instruments can effectively promote sustainable urbanization. Using panel data from 286 prefecture-level cities during 2010–2022, a multi-period Difference-in-Differences (DID) approach is applied, supplemented by dynamic effect analysis, robustness checks, and mediation testing. The findings show that green financial policies significantly enhance urban green development, with effects emerging after a time lag and accumulating steadily over the medium to long term. Mechanism analysis reveals that green technology innovation acts as a critical mediator, indicating that financial support for innovation facilitates environmental performance improvements. Moreover, heterogeneity tests suggest stronger policy effects in economically less-developed cities, reflecting higher marginal returns in regions with weaker green foundations. Overall, the study concludes that green finance serves as an effective institutional tool to correct market failures and accelerate sustainable urban transformation. The implications are twofold: policymakers should strengthen financial innovation and green technology support, and adopt region-specific strategies to maximize policy effectiveness while enhancing the quality of urban green development.